ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BANK UMUM DI INDONESIA - Kartika Wahyu Sukarno; Muhamad Syaichu (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACTS During 2000-2004 Indonesian banking had increased their performance, but in 2005 it had decreased. The objective of this study is to analyze Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), Non Performing Loans (NPL), and Biaya Operasional dan Pendapatan Operasional (BOPO) to Return on Asset (ROA). The financial reports of 84 banks were the population and by using purposive random sampling methods, 59 of them were used as sample. The multiple regression analyzes were used to test hypothesis. The results shows that variables CAR, LDR, and BOPO were significantly influences ROA, but not for variables NPL and DER. CAR, LDR, and NPL have positive influence to ROA, meanwhile BOPO and DER have negative influence. Key words : Performance; ROA; CAR; LDR; NPL; DER; and BOPO